Investigating Arman Shahr in Asi’s Poems - Imamuddin Ibrahimi; Habibullah Haqiqat; Shafigullah Shafaqat (Randwick International of Education and Linguistics Science Journal, 2021)
When the grief around the poet and writer is fragile and when life is filled with sorrow and bitterness, then tyranny and oppression become the ordinary profession of the people in several cases; creator, literary and artistic works as a conscious and connected stratum of society do not became the only spectators, instead with the help of transcendent thoughts and creative minds, they create a valuable creation to be mirror of the dreams and desire of people. On the other hand, they reflects the loud sounds in the face of oppression. Sometimes, the poet and writer thinks calmly in the order to get out of the misfortunes. He takes on idea plane in his mind and throw it. It is the form of al- fadh which the term utopia is more suitable to clarify it. The present study reflects the ideas of the Utopia of Abdul Qahar Asi, the contemporary poet of Afghanistan. In this research, it is tried to identify clear examples of the poet`s word to explain the ideal reading, expression, the dimension and angles of the poet`s utopia. In the continuation of this research, we come to the conclusion that a poet lived in the darkest political situation in Afghanistan who composed a poem and built on utopia to relieve his plan and sorrows. The main indicators of the utopia are the issue of humanity, peace, and love. What he hates and does not want to be in his utopia are war, discrimination, injustice, poverty and selfishness.